Migration and Crime Realities and Media Representations (Springer International Publishing, 2018)
This book proposes an interdisciplinary, multicultural and contemporary approach to examining the controversial links between migration and crime. It includes empirical research on migrants and crime to explore the risk and realities of crime and migration, as well as how mass media in different regions of the world has covered violent acts that have involved migrants (as victims or aggressors). The chapters are written by authors from various countries including the UK, Turkey, Slovenia, Iraq, Albania, Chile, the Republic of Moldavia, and Romania, and from different fields of research including: criminology, sociology, political sciences and communication. They bring to light new ideas, new methodologies and results that could be taken and developed further. This volume allows readers to explore the impact of migration on crime.